Obstructive Sleep Apneas, Cervical Osteophytosis and Sudden Death: A Paradigmatic Case and a Brief Overview of the Literature - Sinelli, Alessandro; Lovati, Carlo; Tien, Thien Trung; Mariani, Claudio (Journal of Sleep And Sleep Disorder Research, 2016)
Obstructive sleep apnea (OSA) syndrome is a common disease characterized by partial or complete collapse of the upper airway during sleep secondary to functional or anatomical factors. The gold standard method for OSA diagnosis is an overnight polysomnogram demonstrating repetitive obstructive apneas and hypopneas during sleep. OSA syndrome is associated with cardiovascular diseases, stroke and rarely with sudden death. OSA and cervical spine osteophytes share some common risk factors, and their coexistence may cause mechanic respiratory obstruction with a severe sleep apnea. We present a brief overview on this syndrome, its links to the cervical spine pathology and their combined effect on a patient presenting with neurological signs who suddenly died before an effective treatment was possible to perform. This case highlights how a rapid deterioration of the functional balance may be possible even when a clinical condition has been present, known and unchanged for a long period of time and the need to treat adequately a not-so-innocuous pathology without an excessive delay.
Keywords: sleep-apnea; cervical osteophytes; sudden death; OSA; CPAP